PERLINDUNGAN HUKUM TERHADAP DANA NASABAH YANG DISIMPAN PADA LEMBAGA PERKREDITAN DESA (LPD) - Hartawiguna Yasa, Putu; Rudy, Dewa Gde; Dharma Kusuma, A. A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013)
Legal protection of customer funds deposited at Village Credit Institutions (LPD). This paper discusses the efforts that are being made by customers to get a refund is deposited at Village Credit Institutions (LPD). In writing this type of scientific journal research is normative research. Village Credit Institutions (LPD) has shown rapid development, Given Regulation Number 8 of 2002 does not clearly regulate the legal protection against customer funds deposited at the LPD, then in case of bankruptcy of LPD due to financial difficulties, very small probability be money (funds) can be accounted for by going back unless Pakraman as owner LPD. At LPD no deposit insurance agency (LPS) as well as banking. Efforts should be made by the customer to get a refund is deposited on the LPD and mediation efforts in court.
Keywords: legal protection, customer funds, LPD